Ataluren treatment of patients with nonsense mutation dystrophinopathy. Issue 4 (October 2014) - Bushby, Katharine; Finkel, Richard; Wong, Brenda; Barohn, Richard; Campbell, Craig; Comi, Giacomo P.; Connolly, Anne M.; Day, John W.; Flanigan, Kevin M.; Goemans, Nathalie; Jones, Kristi J.; Mercuri, Eugenio; et al.
ABSTRACT Introduction: Dystrophinopathy is a rare, severe muscle disorder, and nonsense mutations are found in 13% of cases. Ataluren was developed to enable ribosomal readthrough of premature stop codons in nonsense mutation (nm) genetic disorders. Methods: Randomized, double‐blind, placebo‐controlled study; males ≥5 years with nm‐dystrophinopathy received study drug orally 3 times daily, ataluren 10, 10, 20 mg/kg (N = 57); ataluren 20, 20, 40 mg/kg (N = 60); or placebo (N = 57) for 48 weeks. The primary endpoint was change in 6‐Minute Walk Distance (6MWD) at Week 48. Results: Ataluren was generally well tolerated. The primary endpoint favored ataluren 10, 10, 20 mg/kg versus placebo; the week 48 6MWD Δ = 31.3 meters, post hoc P = 0.056. Secondary endpoints (timed function tests) showed meaningful differences between ataluren 10, 10, 20 mg/kg, and placebo. Conclusions: As the first investigational new drug targeting the underlying cause of nm‐dystrophinopathy, ataluren offers promise as a treatment for this orphan genetic disorder with high unmet medical need. Muscle Nerve50: 477–487, 2014